Investigation of mental training in sports branches - Zengin, S.; Kirkbir, F. (International Journal of Applied Exercise Physiology, 2020)
Researchers are interested in studies on the importance of mental research. It is not enough to be physically ready for success in sports. In addition to being physically good, mental processes are also effective in success. So, psychological factors are important in the success of athletes. The current study examined the athlete's Mental Trainingin terms of demographic characteristics. 236 athletes, 115 men and 121 women, participated in the study. As a data collection tool in the research; "Mental Training Inventory in Sports" developed by Behnke et al. [1] and adapted to Turkish by Yarayan and Ilhan [2] was used. The data were tested primarily by normality tests. T test was used for variables with normal distribution and consisting of two categories, and one-way analysis of variance (ANOVA) for variables with three or more categories. The skewness and kurtosis coefficients between -1.5 and 1.5 indicate that the variable has a normal distribution. When the collected data is examined, it is among the specified values. The internal reliability coefficient of the data was found to be 913. The results of the analysis showed that regular sports and the sports branch make a significant difference to the visualization. In addition, significant differences were detected between amateur and professional athletes from the point of visualization.